Rebo Wekasan Festival (Study on Dynamics and Its Implementation for Demak Society) (Eurasian Journal of Learning and Academic Teaching, 2022)
The celebration of Rebo Wekasan is a part of a vital ritual conducted by collaborative Islamic groups, including Muslims in Demak. They believe in the sacredness of the last Wednesday of Safar month because God sends down 320.000 disasters in the world. This belief leads to them holding a specific ritual to request protection from the tragedies on that day. And this particular ritual is different from what other Muslims do, mainly in Java. That is why the researcher is interested in exploring the phenomena rising by what happens. So it leads to the researcher using the ethnographical approach.